2018
DOI: 10.1155/2018/5198621
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Fractional Integral Formulas for the k-Bessel Function

Abstract: The aim of this paper is to deal with two integral transforms involving the Appell function as their kernels. We prove some compositions formulas for generalized fractional integrals with k-Bessel function. The results are expressed in terms of generalized Wright type hypergeometric function and generalized hypergeometric series. Also, the authors presented some related assertion for Saigo, Riemann-Liouville type, and Erdélyi-Kober type fractional integral transforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Recently, Gurjar et al [1] introduced a multivariable generalized Mittag-Leffler (M-L) function; this function and its special cases have recently found various essential applications in solving problems in physics, biology, engineering and applied sciences (see; [2][3][4][5]). The function is defined for , , , ∈ C and min 1≤ ≤ {R( ), R( ); R( ), R( )} > 0, , > 0; < + R( ); = 1, 2, .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gurjar et al [1] introduced a multivariable generalized Mittag-Leffler (M-L) function; this function and its special cases have recently found various essential applications in solving problems in physics, biology, engineering and applied sciences (see; [2][3][4][5]). The function is defined for , , , ∈ C and min 1≤ ≤ {R( ), R( ); R( ), R( )} > 0, , > 0; < + R( ); = 1, 2, .…”
Section: Introductionmentioning
confidence: 99%
“…Now a days, the recent research outputs are indicating that, the dimension of fractional order calculus (FOC) is tuned into the practical applications on science and engineering. Also, it is found that, the fractional calculus describes in models and respective other physical phenomena (see [6,16,18,19,22,23,24,25,26,37,38,39,45,47,48,49,50]).…”
mentioning
confidence: 99%